ANALISIS SWOT DALAM PENERAPAN MANAJEMEN BERBASIS SEKOLAH MELALUI PROGRAM KANDIDAT SEKOLAH RUJUKAN GOOGLE DI SD NO. 2 MENGWI - Anak Agung Gede Agung; Chindytia; I Gusti Agung Mas Clarissa Kenny Larashati, Frederica; Windiana Putri, Ni Made Ailing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of School-Based Management (SBM) through the Google Reference School Candidate program at SD No. 2 Mengwi using a SWOT analysis approach. This research is motivated by the importance of effective school management in facing technological developments and improving the quality of education in elementary schools. The research method used was descriptive qualitative research with data collection techniques in the form of interviews and documentation. The research subjects included the principal and teachers of SD No. 2 Mengwi. The results showed that the school has several strengths, such as a clear vision and mission, participatory leadership, harmonious relationships among school members, and a digital-based Google Reference School Candidate flagship program. The weaknesses found include limited facilities and infrastructure, limited budget, and a relatively small number of students. The opportunities owned by the school include support from the government, parents, the community, and the development of digital technology in learning. Meanwhile, the threats faced include competition with other schools and student behavioral problems such as bullying. Based on the SWOT analysis results, the implementation of SBM at SD No. 2 Mengwi is considered quite effective in supporting school management and improving the quality of education through digital-based programs.